Legality of Protection of MSME Business Actors In Online Buying and Selling Activities In The Digital Era - Wiwik Sri Widiarty (Jurnal Indonesia Sosial Teknologi, 2024)
The digital revolution has changed various aspects of life, including the trade sector. The development of information & communication technology (ICT) gave birth to renewable business models, such as e-transactions in buying and selling. However, online transaction activities in purchasing and vending also present various challenges, one of which is related to legal certainty for MSME business actors. This research aims to identify legal certainty problems MSME business actors face in online purchasing and vending. The method used in the study is a normative juridical approach that examines legislation. Data was collected through literature studies related to regulations when carrying out online buying and selling transactions, the rights of MSME business actors, and dispute resolution mechanisms. The data analysis method employed in this study is a qualitative analysis using deductive approaches. The research results show that legal clarity for MSME business actors involved in the online buying and selling process in the digitalization era is important in ensuring that trade transactions carried out via digital platforms occur with transparency, security, and by applicable legal Wprovisions. The law governing online purchasing and vending is based on principles stipulated in Article 34(1) of the 1945 Constitution. It is embodied in Legislation No. 20 of 2008 regarding Micro, Small, and Medium Enterprises (MSMEs). This regulation is the basis for all legal regulations governing MSMEs to provide adequate protection for MSME actors.